The Role of Human Resource Management in Enhancing the Professionalism of Educators - Erwin; Mas’ud, Anis Anshari; DJ, Arifhan Ady; Sumarsih (Universitas Sulawesi Barat, 2023)
It is important to reexamine the enhancement of human resource professionalism, particularly in the field of education, specifically for academics. The aim of this research is to determine the application of human resource management in improving professionalism and the influencing factors related to the application of human resource management in enhancing the professionalism of teachers in the Majene regency, West Sulawesi. This qualitative study investigates a social phenomenon, utilizing initial observation, interviews, documentation, and drawing conclusions from the description of the human resource role. The research was conducted in several public high schools in the Majene regency, West Sulawesi. The research findings reveal that enhancing teacher professionalism requires training and enhancing the competencies of each individual involved in teaching activities. The implications of this research can provide insights to schools to offer training for every teacher, focusing on learning attitudes, skills, specific knowledge, and behaviors related to their profession